New record of the genus Peramphithoe Conlan & Bousfield, 1982 (Amphipoda: Ampithoidae) from Brazilian coast, with description of a new species - Souza-Filho, Jesser F.; Guedes-Silva, Elkênita; Senna, André R. (Zootaxa, 2016)
A new species Peramphithoe conlanae sp. nov. is described from Todos os Santos Bay, Bahia, Northeast Brazil. The new species is characterized by the morphology of male gnathopod 1 coxa with anteroventral corner acute, palm transverse bearing a robust seta on the palmar corner and dactylus 2 × palm length, gnathopod 2 with propodus oval, palm extremely acute, concave and lacking processes or robust setae, pereopods 5 and 6 with merus and carpus inflated. This paper increases the number of described species in the genus to 22. It is the first record of the genus Peramphithoe from Brazilian waters.